Business Ready Index on Investment: Indonesia's Strategic Position and Policy Implications - Jonli, Marisha; Putra, Budya Pryanto; Martua, Aleknaek (Monas: Jurnal Inovasi Aparatur, 2025)
The analytical method used is Principal Component Analysis Biplot (PCA Biplot), which enables the identification of relationships among indicators and Indonesia’s relative position compared to other countries which includes ten key indicators: ease of business entry, business location, utility services, labor overall, financial services, international trade, taxation, dispute resolution, market competition, and business insolvency. The analytical methods used is Principal Component Analysis Biplot (PCA Biplot) ,which enables the identifications of relationships among indicators and Indonesia’s relative position compared to other countries. The main recommendation of this study is to accelerate the digitalization of business licensing and investment services and to simplify administrative processes, while simultaneously improving legal certainty in order to create a more conducive, competitive, and sustainable business environment at the global level.